2017
DOI: 10.1055/s-0037-1602387
|View full text |Cite
|
Sign up to set email alerts
|

Role of the LF-SINE–Derived Distal ISL1 Enhancer in Patients with Classic Bladder Exstrophy

Abstract: A genome-wide association study and meta-analysis identified as the first genome-wide significant susceptibility gene for classic bladder exstrophy (CBE). A short interspersed repetitive element (SINE), first detected in lobe-finned fishes (LF-SINE), was shown to drive expression in embryonic mouse genital eminence. Hence, we assumed this enhancer a conclusive target for mutations associated with CBE formation and analyzed a cohort of 200 CBE patients. Although we identified two enhancer variants in five CBE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The etiology of BE remains largely unknown; however, recent findings for familial cases (Froster et al, 2004;Kajbafzadeh et al, 2006;Reutter et al, 2003;Reutter, Hoischen, et al, 2007), from analysis (Messelink et al, 1994;Reutter et al, 2003;Shapiro et al, 1984) of twin studies (Reutter, Qi, et al, 2007), and of reports of BE in individuals with trisomy 21 continue to support an underlying genetic susceptibility (Ebert et al, 2009;Reutter et al, 2006;Reutter et al, 2009). More recently, this susceptibility has been supported by findings from array-based approaches, including common variants identified through genome-wide association studies (Draaken et al, 2015;Reutter et al, 2014;Zhang et al, 2017) and rare variants identified through copy number analyses (Beaman et al, 2019;Draaken et al, 2010;Draaken et al, 2013;Draaken et al, 2015;Jorgez et al, 2014;Lundin et al, 2010;Soderhall et al, 2014;von Lowtzow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of BE remains largely unknown; however, recent findings for familial cases (Froster et al, 2004;Kajbafzadeh et al, 2006;Reutter et al, 2003;Reutter, Hoischen, et al, 2007), from analysis (Messelink et al, 1994;Reutter et al, 2003;Shapiro et al, 1984) of twin studies (Reutter, Qi, et al, 2007), and of reports of BE in individuals with trisomy 21 continue to support an underlying genetic susceptibility (Ebert et al, 2009;Reutter et al, 2006;Reutter et al, 2009). More recently, this susceptibility has been supported by findings from array-based approaches, including common variants identified through genome-wide association studies (Draaken et al, 2015;Reutter et al, 2014;Zhang et al, 2017) and rare variants identified through copy number analyses (Beaman et al, 2019;Draaken et al, 2010;Draaken et al, 2013;Draaken et al, 2015;Jorgez et al, 2014;Lundin et al, 2010;Soderhall et al, 2014;von Lowtzow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic association studies have implicated variation in the ISL1 locus in classic bladder extrophy, yet pathogenic variants in the ISL1 coding region have not been proven (101, 102). Another idea is that the association with the ISL1 locus indicates functional variation of a non-coding genomic region that affects ISL1 expression but this hypothesis has yet to be proven (103). ISL1 is a transcription factor known to be expressed in the region of the forming mouse bladder (102).…”
Section: Bladder Exstrophymentioning
confidence: 99%